2011
DOI: 10.1002/we.512
|View full text |Cite
|
Sign up to set email alerts
|

The impact of turbulence intensity and atmospheric stability on power deficits due to wind turbine wakes at Horns Rev wind farm

Abstract: . (2012). The impact of turbulence intensity and atmospheric stability on power deficits due to wind turbine wakes at Horns Rev wind farm. Wind Energy, 15(1), 183-196. DOI: 10.1002/we.512 The impact of turbulence intensity and atmospheric stability on power deficits due to wind turbine wakes at Horns Rev wind farm Moreover, there is a strong stability directional dependence with southerly winds having fewer unstable conditions while northerly winds have fewer observations in the stable classes.Stable condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
267
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 406 publications
(317 citation statements)
references
References 12 publications
22
267
0
5
Order By: Relevance
“…In the simulations, Vestas V80-2MW wind turbines, with a rotor diameter (D) of 80m and a hub-height (z h ) of 70m, are immersed in the flow. Based on the operational records of Vestas V80−2MW wind turbines reported by Hansen et al 36 , the turbines reach a mean angular velocity of 16.1 rpm when the incoming (upwind) mean wind speed at hub height is U hub ≈ 8 ms −1 . The code is run for a long-enough time to guarantee that quasi-steady conditions are reached.…”
Section: Numerical Setupmentioning
confidence: 99%
“…In the simulations, Vestas V80-2MW wind turbines, with a rotor diameter (D) of 80m and a hub-height (z h ) of 70m, are immersed in the flow. Based on the operational records of Vestas V80−2MW wind turbines reported by Hansen et al 36 , the turbines reach a mean angular velocity of 16.1 rpm when the incoming (upwind) mean wind speed at hub height is U hub ≈ 8 ms −1 . The code is run for a long-enough time to guarantee that quasi-steady conditions are reached.…”
Section: Numerical Setupmentioning
confidence: 99%
“…While summer nocturnal lowlevel jets increase boundary-layer wind speeds (Vanderwende et al 2015;Bonin et al 2015), providing ample wind resources during the summer in the Great Plains, the power deficit, the reduction in power production of downwind turbines located within the wakes, increases with atmospheric stability (Hansen et al 2012). New approaches to yawing upwind turbines in order to improve the power production of downwind turbines (Fleming et al 2015(Fleming et al , 2016 require accurate wake prediction.…”
Section: The Evening Boundary Layer and Turbine Wakesmentioning
confidence: 99%
“…Hansen et al (2012) and Schepers et al (2012) report significantly larger power deficits between the first and second row of turbines while the remaining downstream power deficits were less. We saw a similar effect in the North…”
mentioning
confidence: 93%
“…At an offshore Danish wind farm, Hansen et al (2012) found a strong negative correlation between power deficit and ambient turbulence intensity (i.e., atmospheric stability). Under convective conditions, when turbulence levels were relatively high, smallest power deficits were observed.…”
mentioning
confidence: 93%
See 1 more Smart Citation